LIQUID PARAFFIN EFFECT ON TRANSPIRATION TO IMPROVE GROWTH AND FRUITING OF STRAWBERRY PLANTS - Zuhair A. Dawood (Mesopotamia Journal of Agriculture)
ABSTRACT Field experiment was carried out during 2009/2010 season at Horticulture department field, College of Agriculture/ Mosul University. Four concentrations of liquid paraffin (0,2,4 and 6%) were used as a foliar spray on plant at three dates of application (18/2 , 19/3 , and 21/4). A factorial experiment of eight treatments applied using randomized complete block design. The results could be summarized as following . A significant increase in the percentage of primary leaf water content recorded with Hapil variety as compared with Kaiser's samling variety , but the percentage of secondary leaf water content significantly increased in Kaiser's samling variety. Most treatments of liquid paraffin led to a significant increase in the percentage of primary leaf water content with significant decrease in both percentage of secondary leaf water content and relative transpiration .Application of all liquid paraffin treatments induced leaf area in both varieties , but Hapil variety was superior in a single leaf area as compared with Kaiser's samling . Meanwhile , all treatments caused a significant decrease in the percentage dry matter. Most treatments of liquid paraffin caused a significant increase in average fruit weight , number of fruit per plant , yield per plant and total yield as compared with control . Hapil variety was superior in average weight of fruit but Kaiser's samling variety was superior in number of fruit per plant . Foliar spray of 4% of liquid paraffin was the most effective treatment on yield parameters . Percentage of total soluble solid (T.S.S) and leaf dry matter significantly increased by all liquid paraffin treatments in both varieties . At the same time , the amount of vitamin C increased significantly in fruit of Kaiser's samling variety as compared with Hapil variety.